ANÁLISIS DE CONDICIONES HIGROTÉRMICAS DE LOS ESPACIOS EXPOSITIVOS DE UN MUSEO DE ARTE CONTEMPORÁNEO - Cruz, Mauro Gabriel Garcia Santa; di Santo, Walter Patricio; Cruz, Maria Jimena Garcia Santa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In recent years there has been a significant increase in the number and impact of damage caused by natural disasters, as well as the frequency, extent and duration of extreme weather events. In that sense, the 2030 Agenda for Sustainable Development proposes 17 objectives through which countries will intensify their efforts to combat climate change. Among the goals is proposed to increase efforts to protect and safeguard the world's cultural and natural heritage. This article presents one of the case studies of an ongoing doctoral research that assesses the level of conservation and sustainability in cultural buildings. The case is the Museum of Contemporary Art Beato Angelico, which is located in La Plata, Argentina. The objective is to carry out environmental monitoring of the museum for a period of twelve months. This consists in the recording and analysis of environmental conditions through the continuous measurement of temperature and relative humidity. This article presents the results of the winter measurement of 2015. The spatial characteristics of the rooms and their relative location within the building are considered, it is concluded by determining the behavior of the different exhibition spaces.